Canine neural angiostrongylosis: a case–control study in Sydney dogs. Issue 6 (June 2015) - Walker, AG; Spielman, D; Malik, R; Graham, K; Ralph, E; Linton, M; Ward, MP
<x xml:space="preserve">Abstract</x> Objective To determine the risk factors for canine neural angiostrongylosis in dogs domiciled in Sydney, Australia; geographic location, age, sex, neuter status, weight and breed were assessed. Procedure Case and matched‐control dogs were selected from three veterinary clinics in Sydney. Conditional logistic regression was used to identify factors associated with disease status. A scan statistic was used to identify disease clusters. Results Age (young dogs) and neuter status (entire dogs) were independent risk factors for neural angiostrongylosis diagnosis, and diagnoses predominantly occurred during autumn, with some evidence of spatial clustering. Conclusions Veterinarians in endemic areas should be aware of these risk factors when presented with suspect canine neural angiostrongylosis cases and also should consider advising clients of preventive treatment. Potential human health risks should be further investigated, because urban dog populations might represent a useful sentinel species for disease in humans.